Spectroscopy of nanosized composites silicon-organic polymer/nanoporous silicas: Molecular Solids - Ostapenko, N.; Kozlova, N.; Suto, S.; Watanabe, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Fluorescence and excitation spectra (T = 5–290 K) of nanosized silicon–organic polymers poly(di-n-hexylsilane) and poly(methyl(phenyl)silane) incorporated into porous silica materials MCM-41 and SBA-15 have been studied with varying pore diameter from 2.8 to 10 nm. The controlled variation of the pore diameter in the wide range (2.8–10 nm) permitted us, for the first time, to investigate the optical properties of the polymers on their transition from isolated macromolecules to a film. It is found that this transition depends on polymer type and occurs via the formation of new spatially independent structures of the polymers not observed in the spectra of the film, namely, via the formation of disordered and (or) ordered conformations of polymer chains and clusters.